Examining the role of the learning activity types approach in teachers’ technology integration - Baş, Kader. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Teachers have a crucial role for technology integration, but teacher training programs still have room to be more effective in supporting teachers to integrate technology in their classes. It has been theorized that effective teaching with technology is the result of technological pedagogical content knowledge (TPACK) (Mishra & Koehler, 2009). Learning Activity Types (LAT) is an instructional planning TPACK development approach (Harris, Hofer, Schmidt, Blanchard, Young, Grandgenett, & Olphen, 2010). This study investigated the role of LAT approach in teachers’ technology integration using three measures: the adopted TPACK Survey (Hacıömeroğlu, Şahin & Arcagök, 2014) which is used to investigate self-reported technology integration level, Technology Integration Assessment Rubric (Hofer et al., 2010) which is used to investigate lesson plans, and TPACK-Based Technology Integration Observation Instrument (Hofer et al., 2010) which is used to investigate actual lessons. The study used one-group pretest-posttest pre-experimental design. The participants were 15 teachers from a private school in Istanbul. The survey results indicated that there is an increase in TPACK scores of the teachers . Except TCK scores, they are not statistically significant. Also, there is a statistically significant increase in the lesson plan scores. Additionally, most of the teachers’ observation scores are above the average. The study supports the literature that LAT is an effective strategy for TPACK development and different types of assessment methods are essential to assess TPACK development.
Keywords: Educational technology.; Teachers.